Strategi Meningkatkan Pemasaran Pondok Pesantren Baitul Qur’An di Desa Bangkat Monteh, Brangrea, Taliwang, Sumbawa Barat NTB - Muzayyanah Yuliasih (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The emergence of modern pesantren has led to competition between pesantren. Therefore, managers of Islamic boarding schools must be able to attract customers through marketing to show the community the benefits that Islamic boarding schools provide to customers so that they can build a positive self-image. Marketing strategies are needed to keep up with developments and face increasingly fierce competition in the future. Baitul Qur'an Islamic Boarding School is located in Bangkat Monte, Brang Rea District, West Sumbawa Regency, NTB Province. The average age of the students in this Islamic boarding school is between 5-12 years, with their parents working as laborers and farmers. This community service activity began with an interest in understanding the importance of strategies to increase the marketing of Islamic boarding schools. So that it can increase the number of students in the future. This will be very beneficial for the management of the pesantren and stakeholders in the pesantren environment. The methods used include discussions, workshops and face-to-face. Educational marketing is carried out by Islamic boarding schools through product differentiation, in the form of several diverse educational programs. The educational program includes drawing and coloring lessons to increase the creativity of students and morning walks outside the boarding school environment to improve the health of students and greet residents around the boarding school. Every impact and effect on the results of the strategy, there must always be preparation to anticipate all possibilities, so that when the number of students who experience positive or negative impacts increases, there is a solution.